Extractive Photometric Determination of Rhodium(III) with Cyanex 301 - Gore, M.G.; Salunkhe, S.S.; Raman, Bhanu (Asian Journal of Chemistry, 2012)
A method is proposed for direct spectrophotometric determination of Rh(III) from HCl medium in presence of SnCl2 using cyanex 301 in chloroform. Cyanex 301 is [bis-(2,4,4 trimethylpentyl) dithiophosphonic acid]. A coloured Rh-cyanex 301 complex in organic phase exhibits maximum absorption at 450 nm where absorption of reagent was found to be negligible. The effect of various parameters affecting extraction equilibrium of Rh(III) such as acid concentration, SnCl2 concentration, equilibration time, cyanex 301 concentration, effect of diluents and diverse ions have been studied. The probable composition of the species has been deduced from the extraction data. The method is simple, rapid and sensitive and permits separation of Rh(II) from the other metal ions like Cu2+, Co2+, Mn2+.